WAHDATUL WUJUD DALAM PUISI INDONESIA MODERN: MENDISKUSIKAN PUISI-PUISI EMHA AINUN NADJIB - Jamal D. Rahman (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2016)
Absract: By the early of the 17th century, the Malay-Indonesian poetry began with a controversial issue of tasawuf, that of the wahdatul wujud concept. In the Malay-Indonesian literature, the issue has been reproduced ever since with all the controversy, to the Indonesian literature in modern times, one of which is articulated by Emha Ainun Nadjib. This writing discusses the articulation of that concept in the poetry of Emha Ainun Nadjib, by researching the forms of articulation and answering the question of original and novelty about this concept in his poems. Furthermore, it will also be discussed whether the concept contains speculative ideas or mystical experience. Finally, it is concluded that in Nadjib’s poems, speculative ideas mingled with the expression of mystical experience. With this conclusion, the sustainability of the concept in the modern Indonesian poetry is also an effort to further expand and enrich the depth of its meaning.Abstrak: Puisi Melayu-Indonesia dimulai dengan isu tasawuf yang kontroversial di awal abad ke-17, yaitu faham wahdatul wujud. Dalam sastra Melayu-Indonesia, isu ini direproduksi dari abad ke abad dengan segala kontroversinya, sampai sastra Indonesia di zaman modern yang salah satunya diartikulasikan Emha Ainun Nadjib. Tulisan ini mendiskusikan artikulasi faham wahdatul wujud dalam puisi-puisi Emha Ainun Nadjib, dengan melihat bentuk-bentuk artikulasinya berikut apa yang orisinal dan apa pula yang baru dalam puisi-puisinya menyangkut isu ini. Selain itu,  didiskusikan apakah wahdatul wujud dalam puisi Emha Ainun Nadjib mengandung gagasan spekulatif ataukah pengalaman mistis? Tulisan ini menunjukkan bahwa dalam artikulasi wahdatul wujud Emha Ainun Nadjib, gagasan spekulatif berbaur dengan ekspresi pengalaman mistis. Dengan itu semua, kesinambungan isu tersebut dalam puisi Indonesia modern adalah juga usaha untuk lebih memperluas dan memperkaya kedalaman maknanya.   Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v3i2.5303